SHOW TRIALS OF 1937 OF "SABOTEURS" OF AGRICULTURE IN THE NORT-CAUCASUS REGIONS - Kakagasanov, G I (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with organization and carrying out of regional show trials of representatives of collective and state farm production, as a part of the mass ‘kulak operation’ conducted by Secret police of the USSR (NKVD) according to order No. 00447 of 30 July 1937. The author notes that the show trials were conducted of agricultural ‘saboteurs’: former kulaks, criminals who returned after completion of sentence but continued their anti-Soviet and sabotage operations. Among condemned people were employees of machine and tractor stations, chairmen of district executive committees, secretaries of district committees of the Communist party, heads of procurement centers and bread warehouses, directors of elevators and mills, veterinarians, zootechnicians, and assistants of bacteriological laboratories. Those who were brought to trial were sentenced to the first category (shot) and the second category (exile and deportation for 5-10 years) with the publication in the press. The main objective of these trials was forcing the political climate of fear and hysteria, refocusing the numerous grievances of the peasantry of republics, territories, regions, and districts against the arbitrariness of local authorities to the representatives of lower governing bodies and thereby demonstrating state protection of common rural workers.